Factors predicting admission to extended care facility after distal femoral fracture. Issue 4 (July 2017) - Boin, Michael A.; Narayanan, Shankar; Duren, Dana; Dorweiler, Matthew; Lee, Jessica; Froehle, Andrew; Laughlin, Richard
Abstract : Background: Delayed identification of patients requiring admission to an extended care facility (ECF) after orthopaedic injuries is leading to delays in discharge. The aim of this study was to identify patient factors that predict the need for admission to an ECF after distal femoral fracture. Methods: A retrospective chart review was performed in 176 patients admitted with a distal femoral fracture at a level one trauma center. Patient characteristics, medical comorbidities, and fracture classification were among the variables analyzed. Discriminate function analysis was used to predict if a patient would need an ECF after their hospital stay. Results: Seventy-one patients were included in the final statistical analysis. Of these, 11 men (48%) and 40 women (83%) were discharged to an ECF. Analysis demonstrated that higher American Society of Anesthesiologist (ASA) score ( P <0.001), higher body mass index (BMI) ( P <0.02), diabetes ( P <0.03), and periprosthetic fracture ( P <0.04) for men, while a higher ASA score ( P <0.001) and lower hemoglobin ( P <0.05) for women were the key variables in predicting discharge to an ECF. Using these variables, we developed a predictive equation that correctly classified 95.7% of men and 81.3% of women as requiring an ECF. Conclusions: We were able to distinguish patient factors that predicted discharge to an ECF. Patient care providers can use these findings to proactively identify those who will need an ECF and potentially decrease nonmedical delays in discharge.